Tantangan Public Relation dalam Sektor Publik : Sebuah catatatan awal - Putra, I Gusti Ngurah (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1999)
This paper aims at explaining the challenge that public relations faces in public sector organisations. This is an important topic due to the fact that public organisations in Indonesia in recent years have difficulty in gaining peoples support. One of the main weaknesses of public relations practice in public sector is that they tend to apply press agentry model of public relations; a practice which tends to ignore the important of truth as the essence of information. This paper argues that in order to maintain sustainable support from the people, government has to apply appropriate public relations model. It also shows an example of how local governments in China practice appropriate model of public relations so that people support can be obtained.